Service Quality Analysis of Unej Digital Library Using M-S-QUAL and Importance Performance Analysis Methods - Prasetyo, Beny; Ramadhani, Firlia Dwi Cahya; Nurman Arifin, Fajrin (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2024)
A lot of library services are impacted by the improvement of technologies. With this modification, the traditional library services are now entirely digital. To carry out this digitalization, the Unej Digital Library (UnejDigiLib) application was created by the University of Jember's library. The purpose of developing this application is to improve the effectiveness of library services, which were previously hindered by the COVID-19 epidemic. The UnejDigiLib developer has not yet evaluated the quality of its services since the application's release, so they are unsure of whether the current services satisfy the user needs. The goal of this study is to combine Mobile Service Quality (M-S-QUAL) and Importance Performance Analysis (IPA) in order to assess the UnejDigiLib service's quality based on users perceptions. The M-S-QUAL is used to determine the service quality indicators and examine the gap between their performance and importance. After that, the service indications are mapped using the IPA based on their priority level. The M-S-QUAL dimensions that used are: compensation, privacy fulfillment, content, system availability, efficiency, and privacy. Data collection was carried out through online surveys and interview. The respondents are Unej students who had used and borrowed e-book from UnejDigiLib. The sample was determined using simple random sampling and obtained 287 respondents. The findings indicate that the user expectations have not been met by the UnejDigiLib service's performance. Meanwhile, the IPA analysis's findings indicate that the following indicators are found in quadrant 1: C3 (completeness of the book collection), C5 (suitability of the book collection with the curriculum), C6 (updates to the book collection), and F3 (download speed). This quadrant's indicators are the primary focus for the improvement. The conclusion from these improvement suggestions is that application service providers must coordinate with stakeholders to complete the e-book collection according to customer needs and also require technical updates starting from the features and internal application system to minimize errors due to the system.